(untitled) (Conferencea, 2024)
Demographic policy is one of the main determinants of the security of states and, therefore, of world politics. In the demographic process, political-legal relations are formed into institutional forms of national security. For 11 years in Georgia, demographic security issues have been reflected in almost all high-level political documents. These documents will be reviewed in a scientific article. We would also like to review the role of demographic policy and the expected processes in world politics insecurity issues. Demographic policy is one of the crucial issues in matters of national security. That is why, in 2016, the Parliament of Georgia adopted the "Demographic Security Policy" document. Therefore, the state took responsibility for the implementation of demographic policy in security matters. Georgia is part of the world and therefore follows the recommendations developed by the United Nations Population Fund in all areas, including national security.